2019
DOI: 10.1002/adma.201901570
|View full text |Cite|
|
Sign up to set email alerts
|

Encapsulation of Plasmid DNA by Nanoscale Metal–Organic Frameworks for Efficient Gene Transportation and Expression

Abstract: The intracellular delivery and functionalization of genetic molecules play critical roles in gene‐based theranostics. In particular, the delivery of plasmid DNA (pDNA) with safe nonviral vectors for efficient intracellular gene expression has received increasing attention; however, it still has some limitations. A facile one‐pot method is employed to encapsulate pDNA into zeolitic imidazole framework‐8 (ZIF‐8) and ZIF‐8‐polymer vectors via biomimetic mineralization and coprecipitation. The pDNA molecules are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
134
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 52 publications
(78 reference statements)
1
134
1
Order By: Relevance
“…[10,11,56,57] Furthermore,i ncreasing efforts were devoted to construct biomacromolecule@nanoZIF-8 intracellular delivery systems for protein-and gene-based theranostics. [25,[58][59][60] These applications receive more and more attention because of the high loading efficiency and protecting effect of ZIF-8, and the convenient de novo synthesis process.H erein, we highlighted the importance of the embedding patterns for facilitating and preserving the biofunctionality of abiomacromolecule encapsulated within ZIF-8. Importantly,o ur work demonstrated that the embedding patterns can be controlled by chemical modification of the amino acids of the protein that enabled the modulation of the biofunctionality of proteins@ZIF-8.…”
Section: Resultsmentioning
confidence: 99%
“…[10,11,56,57] Furthermore,i ncreasing efforts were devoted to construct biomacromolecule@nanoZIF-8 intracellular delivery systems for protein-and gene-based theranostics. [25,[58][59][60] These applications receive more and more attention because of the high loading efficiency and protecting effect of ZIF-8, and the convenient de novo synthesis process.H erein, we highlighted the importance of the embedding patterns for facilitating and preserving the biofunctionality of abiomacromolecule encapsulated within ZIF-8. Importantly,o ur work demonstrated that the embedding patterns can be controlled by chemical modification of the amino acids of the protein that enabled the modulation of the biofunctionality of proteins@ZIF-8.…”
Section: Resultsmentioning
confidence: 99%
“…Many biomacromolecules@ZIF‐8, including enzymes@ZIF‐8, were recently developed as robust platform for biocatalysis, biosensing, biobanking and bioprocessing . Furthermore, increasing efforts were devoted to construct biomacromolecule@nanoZIF‐8 intracellular delivery systems for protein‐ and gene‐based theranostics . These applications receive more and more attention because of the high loading efficiency and protecting effect of ZIF‐8, and the convenient de novo synthesis process.…”
Section: Resultsmentioning
confidence: 99%
“…Gene silencing as a kind of gene therapy has now been considered as one of the most promising options to overcome the limitations of traditional cancer therapy. [19][20][21] It can induce sequence-specic inhibition of oncogene expression or translation through the delivery of antagomirs to cancer cells, which makes it possess advantages of high specicity, improved safety, high efficacy and unrestricted choice of targets. 22,23 For example, leucine-rich repeat-containing G protein-coupled receptor 5 (Lgr5) is a novel gastric cancer marker, and silencing its expression with antagomirs could efficiently inhibit cancer angiogenesis.…”
Section: Introductionmentioning
confidence: 99%